2020
DOI: 10.21203/rs.3.rs-57952/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors associated with psychological distress, fear and coping strategies during the COVID-19 pandemic in Australia

Abstract: Background: The COVID-19 pandemic disrupted the personal, professional and social life of Australians with some people more impacted than others. Objectives: This study aimed to identify factors associated with psychological distress, fear and coping strategies during the COVID-19 pandemic in Australia. Methods: A cross-sectional online survey was conducted among residents in Australia, including patients, frontline health and other essential service workers, and community members during June 2020. Psychologic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 22 publications
4
30
3
Order By: Relevance
“…Therefore, giving up tobacco use would potentially aid efforts to tackle not only smoking-related chronic diseases, but also the new infectious-disease threat of COVID-19 [ 17 , 25 ]. Although a recent study argued that risky behaviour increases with increased stress related to the perceived vulnerabilities of COVID-19 [ 15 ], this was not the case in our study.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Therefore, giving up tobacco use would potentially aid efforts to tackle not only smoking-related chronic diseases, but also the new infectious-disease threat of COVID-19 [ 17 , 25 ]. Although a recent study argued that risky behaviour increases with increased stress related to the perceived vulnerabilities of COVID-19 [ 15 ], this was not the case in our study.…”
Section: Discussioncontrasting
confidence: 79%
“…Prolonged lockdown, social distancing, and self-isolation are increasing stress and fear, with the potential upsurge of tobacco use [ 14 ]. In addition, tobacco use may increase due to its use as a coping strategy for the increasing levels of anxiety and stress exacerbated by the isolation and quarantine imposed during COVID-19 [ 11 , 15 ]. The diverse nexus of intertwined biological and socio-ecological factors amid this pandemic alongside the lack of access to health care services may augment the density of depression, suicide, domestic violence, and psychiatric illnesses [ 10 ], resulting in a higher use of tobacco products.…”
Section: Introductionmentioning
confidence: 99%
“…The FCV-19S scores, however, were not found to be significantly different based on other factors such as the sex, age, living with family, and presence of persons infected. Earlier studies indicated that risk factors which increase the fear of COVID-19 include being female, older, smoking, using health care services for COVID-19-related stress, worries related to lockdown, and not living with a family member [ 14 , 18 , 21 23 , 32 ]. Differences between the results of this study and earlier studies are likely to be attributable to social conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Results obtained using FCV-19S have been found to be associated with various factors including socio-demographic and residential environments. Being female, older, smoking, using health care services for COVID-19-related stress, and worries related to lockdown are factors associated with higher FCV-19S [ 14 , 18 , 21 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to that, recently published international literature showed that mental health burden is a serious issue during the COVID-19 pandemic. Elevated prevalence of distress, depression, and anxiety symptoms were observed in various studies [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Thereby, being female, at younger age, student or unemployed, a psychiatric history, or experiencing a greater negative impact on the quality of life pose risk factors for increased depression and anxiety symptoms [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%